Vision-based system for simultaneous monitoring of shaft rotational speed and axial vibration using non-projection composite fringe pattern. (1st April 2019) - Zhong, Jianfeng; Zhong, Shuncong; Zhang, Qiukun; Maia, Nuno; Shen, Yaochun; Liu, Shulin; Yu, Yingjie; Peng, Zhike
Highlights: Vision-based simultaneous monitoring of shaft IRS and axial vibration was proposed. Composite fringe pattern and linear array sensor were employed in the measurements. It demonstrated high-precision performance of IRS and axial vibration measurements. Abstract: Both the instantaneous rotational speed (IRS) and vibration of a rotating shaft are key information for condition monitoring and faults diagnosis of rotary machinery. Instead of using a rotational speed encoder and a displacement sensor to measure the IRS and the vibration of a rotating shaft, a non-projection fringe pattern and vision-based system was proposed to realize simultaneous measurement of IRS and axial vibration of a rotation shaft. A composite fringe pattern (CFP) was pasted around the surface of the shaft and worked as IRS and displacement sensors. Each line fringe intensity along the axial direction contained two fringe period densities (FPDs), in which each FPD ratio only corresponds to a rotational angle. A linear array image sensor was employed to record the fringe intensity, from which the time domain rotational angle could be obtained from the change of the FPD ratio and the axial displacement could be acquired by locating the maximum peaks of the cross correlation between the recorded fringe intensity and the reference one. Thus, the IRS could be obtained accurately and efficiently from the rotational angle by multiplying the sampling frame rate of the high-speed camera. Simulated and experimental results demonstrated that the proposed system could simultaneously extract the IRS and axial displacement with the advantage of non-contact and effectiveness. Therefore, the proposed system provides an alternative vision-based approach for the simultaneous measurement of IRS and axial vibration.